The relationship between perceived parenting styles and stress levels among Malaysian secondary school students - Tay, Ee Lin *; Tam, Cai Lian * (Sunway University College, 2010)
This research aimed to investigate the relationship between parenting styles and stress level among Malaysian adolescents. A final sample of 140 participants with equal number of males and females, with ages ranging from 13 to 16 years old were recruited. Data collection was conducted in two public secondary schools in Pahang. This survey included three instruments: Parental Authority Questionnaire (PAQ), Adolescent Stress Questionnaire (ASQ) and demographic questionnaire. The results showed mothers prefer authoritative parenting compared to fathers and that parenting styles are not related to adolescents? stress level. There was also no gender difference in adolescents? stress level in home-life, peer pressure and school performance. Recommendations for future studies and implications of study are discussed.